Current Trends in Computer Science and Mechanical Automation Vol. 2 : Selected Papers From CSMA2016 - Shawn X. Wang (De Gruyter Open Poland, 2017)
No detailed description available for'Current Trends in Computer Science and Mechanical Automation Vol. 2'.